PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 23 PADANG - Arnilawati, Arnilawati; Aima, Zulfitri; Febriana, Rina (STKIP PGRI Sumbar, 2013)
The comprehension in mathematics concept for students is still low becomes a basic of this research. The purpose of this research is to know what is the comprehension of mathematic concept for cooperatif learning type Pair Check better than for implementation of convensional learningâs students for grade VIII SMPN 23 Padang in 2012/2013. The type of this research is experimental research by using random planning focused on subject. The populations are students in grade VIII SMPN 23 Padang in 2012/2013, which consist of five classes. Moreover, sample of this research is taken by random, VIII1 is for experimental class and VIII2 is for control class. The instrument of this research is the comprehension of mathematics concept test. The techniques of data analysis is using t test for one group by software MINITAB is got P-value = 0,013 smaller thanÂ Â = 0.05, so this hyphothesis is accepted. In conclusion, the comprehension of mathematics concept for implemented convensional learningâs students